Hubungan Antara Self Disclosure dengan Personal Adjustment Mahasiswa Rantau Asal Kalimantan Tengah - Kathryn Trifosa Hutabarat; Dewita Karema Sarajar (Jurnal Ilmiah Universitas Batanghari Jambi, 2026)
This study was conducted with the aim of determining the relationship between self-disclosure and personal adjustment of out-of-town students from Central Kalimantan. This research is a correlational study using a quantitative approach. The subjects in this study were 50 out-of-town students from Central Kalimantan who were active undergraduate students (S1) studying at Satya Wacana Christian University. Sampling was conducted using a quota sampling technique. The data collection method used a self-disclosure scale, namely The Development of the Self-Disclosure Scale, and for the personal adjustment scale, namely the Multidimensional Adjustment Scale. The data analysis technique used was a prerequisite test that included normality and linearity tests. Based on the results of the study, there is a significant and positive relationship between self-disclosure and personal adjustment in out-of-town students from Kalimantan at Satya Wacana Christian University. This means that the higher the level of self-disclosure carried out by out-of-town students, the higher the success of the individual in making good personal adjustment. Conversely, the lower the level of self-disclosure carried out, the lower the individual's success in being able to make good personal adjustment.